THE ROLE OF EXTENSION WORKERS IN CONDUCTING COUNSELING ON ORGANIC VEGETABLE CULTIVATION TO HOUSEWIVES IN THE BRENJONK COMMUNITY, PENANGGUNGAN VILLAGE, MOJOKERTO REGENCY - Rachma Dini Fitria (SOLIDARITY: Journal of Social Studies, 2022)
Agricultural extension is perceived only to achieve production targets and technology transfer. The limited number of extension workers further adds to the ongoing problem of agricultural extension. The government has begun to seek to increase the workforce of extension workers by involving independent and private extension workers. The Brenjonk community is an example of an organic farmer group that was built by self-help extension workers. The limited funds and the independent extension workers involved are the main obstacles in the extension process. This study will analyze the role of self-help extension workers as well as efforts to increase changes in the behavior of housewives. The method used is descriptive qualitative and Spearman rank correlation analysis. The results of this study indicate that self-help extension workers have performed their roles as facilitators, mediators, dynamists, and mediators. Housewives have been able to apply organic vegetable cultivation on their land because it has become a habit. The recommended extension model to improve the behavior of housewives is to involve them in discussion activities with extension workers, increase the number of stakeholders involved in counseling, increase the use of local resources, and increase the assistance of housewives